Respuesta :
Isolate the variable on one side of the equation and everything else to the opposite side of the variable.
You can isolate the variable by undoing the operations done to the variable.
For example, if we added 5 to x (x + 5) then we would need to undo that operation. We would need to use the inverse of addition. Which is subtraction.
5x + 6 = 2(2x - 3)
5x + 6 = 4x - 6 <-- Distribute the 2
x + 6 = -6 <-- Subtract 4x from each side
x = -12 <-- Subtract 6 from each side
So, x is equal to -12.
You can isolate the variable by undoing the operations done to the variable.
For example, if we added 5 to x (x + 5) then we would need to undo that operation. We would need to use the inverse of addition. Which is subtraction.
5x + 6 = 2(2x - 3)
5x + 6 = 4x - 6 <-- Distribute the 2
x + 6 = -6 <-- Subtract 4x from each side
x = -12 <-- Subtract 6 from each side
So, x is equal to -12.
The solution to the equation 5x + 6 = 2(2x – 3) is x = -12
The given equation is:
5x + 6 = 2(2x - 3)
Expand the right hand side of the equation using distributive rule
5x + 6 = 4x - 6
Collect like terms
5x - 4x = -6 - 6
Simplify the equation above
x = -12
Therefore, the solution to the equation 5x + 6 = 2(2x – 3) is x = -12
Learn more here: https://brainly.com/question/4396988